2019
DOI: 10.1021/acs.bioconjchem.9b00719
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Protein Photochemical Covalent Attachment to Carbon Nanotube Side Walls and Its Electronic Impact on Single Molecule Function

Abstract: Dafydd 2020. Site-specific protein photochemical covalent attachment to carbon nanotube side walls and its electronic impact on single molecule function. Bioconjugate Chemistry 31 (3) , pp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 62 publications
3
40
0
Order By: Relevance
“…The GFP variant containing the non-canonical amino acid p-azido-L-phenylalanine (AzF) in place of residue Gln204 (Figure S2) was generated as described previously using an expanded genetic code approach [36][37][38]. The variant, termed GFP 204AzF , was used because the AzF (and thus the linking site) lies close to the chromophore of GFP and has previously been shown to retain function on the attachment to SWCNTs and DNA [7,11,38]. To functionalize GFP with DNA, amine-modified DNA was reacted with BCN-NHS ester (see Figure S3 for details).…”
Section: Production Of Azide-gfp and Functionalization Of Gfp With Dnamentioning
confidence: 99%
See 3 more Smart Citations
“…The GFP variant containing the non-canonical amino acid p-azido-L-phenylalanine (AzF) in place of residue Gln204 (Figure S2) was generated as described previously using an expanded genetic code approach [36][37][38]. The variant, termed GFP 204AzF , was used because the AzF (and thus the linking site) lies close to the chromophore of GFP and has previously been shown to retain function on the attachment to SWCNTs and DNA [7,11,38]. To functionalize GFP with DNA, amine-modified DNA was reacted with BCN-NHS ester (see Figure S3 for details).…”
Section: Production Of Azide-gfp and Functionalization Of Gfp With Dnamentioning
confidence: 99%
“…This has been shown to have significant effects in the protein/SWCNT interactions. Zubkovs et al and Thomas et al [11,21] have shown how the site-specific attachment of a fluorescent protein affects the optical behavior of both protein and SWCNTs; this was demonstrated by investigating the change in a fluorescent protein function and, in the case of Zubkovs et al, of (7,6) SWCNTs within a mixture of nanotubes. There are other examples of changes in the fluorescent behavior of SWCNTs due to biofunctionalization, but these investigations are typically carried out with unsorted SWCNTs; hence, the interaction can only be considered an average response to each species in the mixture.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…13). 60 Depending on the position of the protein on the CNT side wall, GFP function switched from GFP LA and GFP SA , which resulted in a change of the fluorescence wavelength.…”
Section: Carbon Nanotubesmentioning
confidence: 99%